2022
DOI: 10.1186/s13006-022-00504-6
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal mental health, breastfeeding beliefs, and breastfeeding practices in rural China

Abstract: Background The importance of breastfeeding in low- and middle- income countries is well recognized, yet the importance of postnatal mental health on breastfeeding practices and beliefs in these settings has been understudied. This study investigates the associations between maternal mental health problems, breastfeeding beliefs and breastfeeding practices in rural China. Methods Cross-sectional data were collected in November and December 2019 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In a recent systemic review, 12 of 33 studies reported significant positive effects of behavioral interventions on maternal mental health and breastfeeding success [ 23 ]. On the other hand, a previous study showed a significant relationship between maternal symptoms of mental health problems and breastfeeding self-efficacy [ 24 ], showing the importance of multi-dimensional interaction [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systemic review, 12 of 33 studies reported significant positive effects of behavioral interventions on maternal mental health and breastfeeding success [ 23 ]. On the other hand, a previous study showed a significant relationship between maternal symptoms of mental health problems and breastfeeding self-efficacy [ 24 ], showing the importance of multi-dimensional interaction [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that breastfeeding mothers are more susceptible to mental illnesses (Jiang et al, 2022;Krol & Grossmann, 2018). The COVID-19 outbreak in Indonesia has exacerbated this vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that, compared to urban residents, those living in rural areas or a distance from major cities often encounter difficulties accessing BFHs [ 22 ]. Additionally, individuals with higher SES may prefer giving birth at prestigious hospitals, which are more likely to be BFHs [ 23 , 24 ]. Accordingly, it is highly conceivable that a complex interplay exists among SES, giving birth at BFHs, and EBF.…”
Section: Introductionmentioning
confidence: 99%